Penyalahguna Narkotika di Indonesia: Apakah Mereka Korban atau Pelaku? - Mahfud Mahfud; Faisal A. Rani; Rizanizarli Rizanizarli (Pancasila and Law Review, 2021)
It is unprecedented that the Act Number 35, 2009 on Narcotics has incorporated the term of victims towards illegal users of narcotics which cannot be convicted for the crime and provided them with treatment at special rehabilitation center as worded in Article 103 (1) (b) of the Act. However, Article 103 (1) (a) of the Act also provides the possibility for those using narcotics illegally to be convicted. It causes law enforces might find it difficult to differentiate between victims and criminals concerning this violation. This research aims to discuss the definition of illegal narcotic users under the Narcotic Act 2009 and the criteria used by law enforcers in distinguishing between victims and criminals. This is a juridical normative research by using the method encompassing document analysis of the Narcotic Act 2009 and other relevant laws will be adopted in discussing the issue. This research reveals that the Act recognises the users of illegal narcotics as fully victims if they use narcotics with a certain amount for themselves only and considers the illegal narcotics users as criminals if they provide the substances for other people. The Act has governed illegal using of the substances in Articles 1 points (13), (15), 7, 111, 112, and 114. Surprisingly, the Act provided both fully victims and victims of being found guilty first treatment in the rehabilitation centre for certain period.